Design of MIDI decoder and controller program for MIDI auto saxophone - Muhammad Halifi, Muhamad (2013)
The saxophone is a musical instrument that lends itself to be controlled electronically. When air is blown into the mouthpiece, tones are produced through a combination of saxophone key pressd. A MIDI decoder program is used to extract the MIDI data that send by the computer and send the instructions to the controller program. the controller program sends the instruction signals to the 18 servo motors to depress the saxophone keys and solenoid valve to control the air flow into the saxophone mouthpiece. Each of the 30 musical notes is programmed to get the correct press of saxophone keys combination. An array of 18 switching signal is used for determining which tones to be produced by the saxophone. This cause the significant signal delay to produce a lag between the data input and key presses. At the end of the project, the MIDI decoder was able to deliver correct switching signals according to the saxophone fingering chart although there was a lag between the data input and key presses on the saxophone.